Imaginer la mort : les topographies mémorielles de Shimon Attie - Massicotte, Claudie (RACAR : Revue d'art canadienne / Canadian Art Review, 2011)
Visual artist Shimon Attie’s project Finstere Medine consists of a series of archival images that were first projected onto buildings in Berlin, then photographed by the artist for future exhibitions in museums. Representing Jewish victims of the Second World War, these archival images at times relocated their characters at the exact location they had occupied before the extermination. At other times, they relocated these victims in newly developed buildings or areas of the city. The present article suggests that Attie’s project probes the role of architecture with regards to its relationship with the past, and explores new avenues of reflection on the work of mourning that always defines architectural commemorations of historical violence.